Pengaruh Pemberian Edukasi Menggunakan Buku Saku Bergambar dan Berbahasa Madura terhadap Tingkat Pengetahuan Penderita dan Pengawas Menelan Obat Tuberkulosis Paru (The Effect of A Pictorial Booklet with Madurese Language on Level of Knowledge among Tuber - Lailatul Maghfiroh; Antonius Nugraha Widhi Pratama; Ema Rachmawati (Pustaka Kesehatan, 2017)
Tuberculosis (TB) has become one of major health problems. Successful treatment of pulmonary TB is determined by patient adherence. One of the factors that influences poor patient adherence is the lack of knowledge in TB among patients and treatment observer. Improving this knowledge is therefore necessary. This study was conducted with the aim to analyze the effect of education using a booklet with pictures and Madurese language on the TB knowledge level of patients and treatment observer. This study used a quasi-experimental study design with one group pre-test and post-test. This research was conducted in Kaliwates, Patrang, and Mayang health centers, Jember Regency. The level of knowledge was evaluated using a 16 item questionnaire at the time before the booklet was given and 1-2 weeks after. The result of paired T-test analysis showed a statistically significant increase (p<0.001) of TB knowledge level before (10.18 ± 1.781) and after (11.88 ± 1.686) the education using the booklet. In conclusion, the use of a booklet containing illustrated pictures and local language may improve the level of knowledge of TB patients and their treatment observer. Keywords: tuberculosis, tuberculosis treatment observer, health education, booklet, Madurese language